Broken Bonds: How Capitalism, Globalization, and Technology Erode ‘Asabiyyah - Hafis, Ade; Hisbullah, Muhammad Ali; Ibrahim, Malik; Yusrizal (Universitas Islam Negeri Sunan Kalijaga Yogyakarta, 2025)
Ibn Khaldun, in his Muqaddimah, explained that the cycle of civilizational rise and decline is determined by the strength of ‘asabiyyah. Although various studies have examined the relevance of ‘asabiyyah, particularly within contemporary Muslim societies, the relationship between modernization processes and civilizational collapse within the framework of ‘asabiyyah remains largely underexplored. This study aims to analyze the relevance of ‘asabiyyah in understanding the dynamics of modern civilizations, specifically investigating the impact of capitalism, globalization, and technological advancement on the potential for civilizational decline, using the historical cases of the Soviet Union and Nazi Germany. The research adopts a descriptive qualitative approach through a literature review of books and national and international journal articles focusing on ‘asabiyyah. Data were collected through systematic and selective searches across leading databases such as Google Scholar, PubMed, and Scopus. Data analysis was conducted using meta-analysis techniques to identify major themes, compare arguments, and construct a theoretical synthesis from various sources. The findings of this study indicate that the erosion of ‘asabiyyah can accelerate the internal vulnerabilities of a civilization, as reflected in the historical cases of the Soviet Union and Nazi Germany. The findings of this study underscore the critical importance of strengthening collective identity and social solidarity as prerequisites for the resilience of modern civilizations, while also encouraging comparative studies that integrate Ibn Khaldun’s classical theory with contemporary theories of social solidarity, globalization, and cultural identity. Ibn Khaldun dalam Muqaddimah menjelaskan siklus kemajuan dan kemunduran peradaban ditentukan oleh kekuatan ‘asabiyyah. Meskipun berbagai penelitian telah mengkaji relevansi ‘asabiyyah khususnya di masyarakat Muslim kontemporer, namun keterkaitan antara proses modernisasi dan keruntuhan peradaban dalam kerangka ‘asabiyyah masih jarang dibahas. Penelitian ini bertujuan untuk menganalisis relevansi ‘asabiyyah dalam memahami dinamika peradaban modern, khususnya pengaruh kapitalisme, globalisasi, dan kemajuan teknologi terhadap potensi kemunduran peradaban dengan mengambil kasus historis Uni Soviet dan Nazi German. Penelitian ini menggunakan pendekatan kualitatif deskriptif dengan studi pustaka terhadap buku-buku dan artikel jurnal nasional dan internasional yang berfokus pada ‘asabiyyah. Data dikumpulkan melalui pencarian sistematis dan selektif dari berbagai database terkemuka seperti Google Scholar, PubMed, dan Scopus. Analisis data dilakukan dengan teknik meta-analisis untuk mengidentifikasi tema-tema utama, membandingkan argumentasi, dan menyusun sintesis teoritis dari berbagai sumber. Temuan penelitian menunjukkan bahwa erosi ‘asabiyyah dapat mempercepat kerentanan suatu peradaban, sebagaimana tercermin pada kasus Uni Soviet dan Nazi Jerman. Implikasi penelitian ini menegaskan pentingnya memperkuat identitas kolektif dan solidaritas sosial sebagai prasyarat ketahanan peradaban modern, serta mendorong kajian komparatif yang mengintegrasikan teori klasik Ibn Khaldun dengan teori-teori kontemporer mengenai solidaritas sosial, globalisasi, dan identitas budaya.